Determination of the Effectiveness of Dental Measures for the Prevention of Periodontal Dental Diseases in Workers of the Production of Metal Structures - Abdulaxatov Abdugaffor Abdusattor ugli; Islamova Nilufar Bustanovna (Scientific Trends, 2024)
In the process of intensive industrial development, the study of the role of harmful and health-related factors of the production environment is timely and very important. After all, unfavorable working conditions contribute to the formation of various pathological processes in the human body (Amirov N.H., 2018).